Changes of Real Estate Sector in Context of Economy Lithuania - Misiūnas, Algimantas (Lithuanian Journal of Statistics, 2011)
The paper analyses macroeconomic and financial ratios of Lithuanian enterprises (real estate enterprises) in the periodfrom 1998 to 2010. During the period in question, which was selected consciously and purposefully, Lithuanian economyexperienced two recessions: the first one took place after the Russian crisis 1998, the second one started in 2008, together with theglobal financial crisis. In the period between the two crises, a rapid economic development was observed.The efficiency is assessed using various financial ratios, reflecting various aspects of performance of an economic entity: itscapability to secure income, to perform profitably, to properly manage liabilities, to make proper use of available potential, to avoidjeopardising its further performance. Since no common methodology for the assessment of economic efficiency has been developedyet, it is offered to form an integral aggregate ratio to make possible the intercomparison of economic sectors and to determine thelevel of efficiency based on a set of financial ratios, not on each of them separately.